Fulminant fournier's gangrene in a 39-year-old male sailor with poorly controlled diabetes mellitus: A case report - Wibawa, Putu Chandra; Wiradana, Anak Agung Anom; Putra, Agung Ngurah Rai Kusuma (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2026)
Fournier’s gangrene is an uncommon yet potentially fatal form of necrotising fasciitis that involves the genital, perineal, and perianal regions, with mortality rates approaching 40%. We describe a case involving a 39-year-old male sailor who presented after 10 days of progressive scrotal swelling that had extended to the buttocks, along with purulent discharge, intense pain, and fever. The patient had a background of poorly managed diabetes mellitus and chronic alcohol use. On physical examination, necrotic changes were noted in the scrotal and perianal areas. Laboratory findings revealed elevated white cell count, hyperglycemia, hyponatremia, hypokalemia, and hypoalbuminemia. Culture results identified Proteus mirabilis and Klebsiella pneumoniae subspecies pneumoniae. Emergency surgical debridement and necrotomy were performed, followed by antibiotic therapy (ceftriaxone and metronidazole), fluid replacement, pain management, and insulin administration. This case underscores the critical need for early recognition and timely surgical treatment in managing Fournier’s gangrene, especially in patients with risk factors such as diabetes and alcohol use. Occupational demands that delay medical consultation may worsen disease severity and complicate therapeutic efforts.